Tazobactam/ceftolozane and tobramycin combination therapy in extensively drug-resistant Pseudomonas aeruginosa infections in severe burn injury: a case report - Yuta Ibe; Ryuichiro Kakizaki; Hirotoshi Inamura; Tomoyuki Ishigo; Yoshihiro Fujiya; Hiroyuki Inoue; Shuji Uemura; Satoshi Fujii; Satoshi Takahashi; Eichi Narimatsu; Masahide Fukudo (BMC, 2023)
Abstract Background Combination therapy with tazobactam/ceftolozane (TAZ/CTLZ) and high-dose aminoglycosides has been reported to be efficacious in extensively drug-resistant (XDR)-Pseudomonas aeruginosa infection. However, there are no reports of efficacy in XDR-P. aeruginosa infection for combination therapy with low-dose aminoglycosides and TAZ/CTLZ. Herein, we describe a rare case of severe burn injury patients with persistent bacteremia due to XDR-P. aeruginosa, which was successfully treated with TAZ/CTLZ and low-dose tobramycin (TOB). Case presentation A 31-year-old man was admitted to the intensive care unit with severe burn injury involving 52% of the total body surface area and a prognostic burn index of 79.5. The patient had recurrent bacterial infections since admission, and blood cultures collected on the 37th day of admission revealed the presence of P. aeruginosa strains that were resistant to all β-lactams and amikacin (AMK). The results of the antimicrobial synergistic study showed no synergistic effect of low-dose meropenem (MEPM) and AMK combination therapy. The patient had acute renal failure, and it was difficult to increase the dose of MEPM and AMK, respectively. Thus, we initiated TAZ/CTLZ 1.5 g/8 h instead of the AMK and MEPM combination therapy on the 43rd day of hospitalization. Low-dose TAZ/CTLZ was continued because of prolonged renal dysfunction and resulted in a transient clinical improvement. However, the dosage of TAZ/CTLZ could be increased as the renal function improved, but despite an increased TAZ/CTLZ dose, bacteremia persisted, and the blood cultures remained positive. Thus, TOB was added to TAZ/CTLZ at low doses for synergistic effect against Gram-negative bacteria. Blood cultures collected after initiation of combination therapy with TAZ/CTLZ and low-dose TOB were negative on two consecutive follow-up evaluations. Thereafter, although the patient had several episodes of fever and increased inflammatory response, blood cultures consistently tested negative, and all of the wounds healed. On the 93rd day, due to the good healing progress, the patient was transferred to another hospital. Conclusions TAZ/CTLZ and low-dose TOB combination therapy showed the potential for synergistic effects. Our present report suggests a novel synergistic treatment strategy for rare cases that are refractory to the treatment of infections, such as XDR-P. aeruginosa infection.